Local effect of simvastatin combined with different osteoconductive biomaterials and collagen sponge on new bone formation in critical defects in rat calvaria - Sousa,Dircilei Nascimento de (2020)
Abstract Purpose To evaluate the local effect of simvastatin (SVT) combined with deproteinized bovine bone (DBB) with hydroxyapatite/β-tricalcium phosphate biphasic ceramics (HA/TCP) and with collagen sponge (CS) on bone repair in critical size defects (CSDs) in rat calvaria. Methods Forty-two 5-mm diameter CSDs were made bilaterally in the calvaria of 18 rats. The animals were allocated according to the type of biomaterial and associations used to fill the CSD. After 8 weeks, the animals were euthanized, and their calvaria were evaluated for repaired tissue composition using histologic and histometric analyses. Results In the histometric analysis, the use of SVT showed to increase bone formation in the CSDs when combined with all the bone substitutes tested in this study (p<0.05). Greater bone formation was observed in the groups with SVT compared to the groups without SVT. Conclusions The use of SVT without the need for a vehicle and combined with a commercially available biomaterial may be a cheaper way to potentiate the formation of bone tissue without the need to produce new biomaterials. Therefore, SVT combined with DBB induced significantly greater new bone formation than did the other treatments.